Full-Range Leadership Theory: Preferred And Perceived Leadership Styles In The Malaysian Life Insurance Industry - Yin, Ho Sze (2008)
This study aims to explore the preferred and perceived leadership of life insurance agents among the top insurance players in Malaysia to pinpoint areas of improvements, which could be used as insurance leaders\' guides. Beside that, this study also aims to examine the relationship and impact of the perceived leadership styles on agents\' job satisfaction.